Relationship Between Preeclampsia and Anemia with The Risk of Uterine Atony - Suhartik (LPPM Universitas Mohammad Husni Thamrin, 2025)
Preeclampsia-eclampsia causes changes in vital organs, one of which is endothelial cell dysfunction. Preeclampsia carries a risk of uterine atony because when the mother experiences preeclampsia, endothelial cell damage occurs, causing exposure of endothelial cells to toxic lipid peroxides that circulate throughout the body and cause the myometrium muscle to not contract, resulting in uterine atony. Anemia carries a risk of uterine atony due to a lack of hemoglobin to deliver oxygen and nutrients, resulting in the uterus lacking the ability to contract, resulting in uterine atony. The purpose of this study was to determine the relationship between preeclampsia and anemia with the risk of uterine atony at Aisiyah Hospital, Bojonegoro Regency. This study is a quantitative study with a descriptive correlative design and a cross-sectional approach. The data collection technique was total sampling, meaning all populations were sampled. The data collection methods used in this study were observation, interviews, questionnaires, and documentation. The data analysis used in this study was multiple linear regression. Based on the analysis results, the p value of the preeclampsia variable (0.000) < α (0.05) was obtained, so H0 was rejected, meaning there was a relationship between preeclampsia and the risk of uterine atony. Meanwhile, the analysis results of the p value of the anemia variable (0.000) < α (0.05) were obtained, so H0 was rejected, meaning there was a relationship between anemia and the risk of uterine atony.